Financial Barriers and Response Strategies to Support Women Entrepreneurs in Rural Nigeria - Peter, Wuraola (Université d'Ottawa / University of Ottawa, 2021)
Women entrepreneurs play increasingly important roles in job creation and sustainable economic growth in developing economies, including sub-Saharan Africa. While Nigeria has made progress in closing gender gaps in women’s employment rights, financial inclusion and access to resources remain challenges for many women who seek to start and grow businesses. Barriers to venture creation are particularly problematic for women entrepreneurs living in rural Nigeria. Yet, few studies have examined women entrepreneurs’ access to capital in the context of rural Nigeria, including the perceived value of informal lenders and government support programs. This thesis informs the literature by reporting on women entrepreneurs who own and operate retail micro-enterprises in rural, South-West Nigeria, specifically Atakunmosa West, Osun State. The study findings demonstrate the value and limitations of informal lenders, such as Ajo and Esusu, in bridging institutional voids in banking practices and technology-enabled money services. Drawing on the social feminist and resource-based theory, the study advances a conceptual model of the gendered context of financial inclusion and considers the implications for research and policy.
Keywords: Women entrepreneurs; Financial inclusion; Nigeria; Small business; Micro-credit; Micro-enterprise; Finance; Developing economies; Esusu; Ajo